2015
DOI: 10.5935/1806-6690.20150006
|View full text |Cite
|
Sign up to set email alerts
|

Productive characteristics, nutrition and agronomic efficiency of polymer-coated MAP in lettuce crops

Abstract: -In contrast to enhanced-efficiency nitrogen fertilisers, principally urea, phosphate fertilisers have been little studied and the available information is limited. The aim of this work therefore was to evaluate the productive and nutritional characteristics and the agronomic efficiency of a polymer-coated MAP fertilizer on two subsequent lettuce crops. The experiment was carried out in a greenhouse, in pots with a capacity of 4 kg, filled with a dystrophic yellow Latosol of a clayey texture. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
3
12
0
1
Order By: Relevance
“…These results agree with those of Corrêa et al (2008) in maize crops and Chagas et al (2015) in two lettuce crops, who observed a reduction in phosphorus use efficiency with dosage increases. However, Chagas et al (2015) found increased phosphate efficiency with polymer-coated MAP fertilizer in both lettuce crops, improving residual phosphorus used, but not for onions (Chagas et al, 2016). However, increased nutrient availability and the source used are not the only factors that can alter the efficiency rate.…”
Section: Nutrient Utilization Efficiencysupporting
confidence: 82%
“…These results agree with those of Corrêa et al (2008) in maize crops and Chagas et al (2015) in two lettuce crops, who observed a reduction in phosphorus use efficiency with dosage increases. However, Chagas et al (2015) found increased phosphate efficiency with polymer-coated MAP fertilizer in both lettuce crops, improving residual phosphorus used, but not for onions (Chagas et al, 2016). However, increased nutrient availability and the source used are not the only factors that can alter the efficiency rate.…”
Section: Nutrient Utilization Efficiencysupporting
confidence: 82%
“…A similar strategy could be applied with additives of iron and aluminum affinity (responsible for the fixation of phosphorus in the soil) in P fertilizers, increasing its agronomic efficiency. Reis Jr and Silva (2012), Chagas et al (2015), Chagas et al (2016) carried out studies on P fertilizer coated with anionic polymers (Policote) that reduce the activity of iron and aluminum to evaluate the efficiency of P fertilization. The need to increase the efficiency of P fertilization and the lack of information about enhanced efficiency P fertilizer justifies studies to evaluate the performance of this kind of fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…The coating of phosphate fertilizers with anionic polymers with affinity for cations such as aluminum and iron may attenuate the adverse effects of soil P precipitation and increase the efficiency of phosphate fertilization (Chagas et al, 2015;2016a;2016b). Adding both Mg and anionic polymers to the coating may result in increased P uptake and coffee plant growth compared with other phosphate fertilizer technologies, such as resincoated fertilizers, which decrease the rate of P released from the fertilizer granule to the soil (Huett;Gogel, 2000;Du;Zhou, 2006;Broschat;Moore, 2007;Sanders et al, 2012;Adams;Frantz;Bugbee, 2013).…”
Section: Introductionmentioning
confidence: 99%